Toxicity standards of biosolid leachate - Alexandre, Rafael Lucas; Manzatto, Caroline Menezes; Giacobbo, Emilly; Florentino, Robert Willian; Martins, Kelly Geronazzo (Revista Brasileira de Ciência, Tecnologia e Inovação, 2024)
Sewage treatment in Brazilian cities generates biosolids that can be useful in the agricultural field, although they pose contamination risks to the environment and to human health. Ecotoxicity tests are essential to ensure the safety of such a use, since they assess biosolids’ toxicity in the soil and in water. The aim of the current study is to assess biosolids leachate phytotoxicity by using lettuce seeds. In order to do so, Petri dishes were used to incubate the seeds, which received the biosolids leachate and remained under controlled temperature conditions, in the dark, for 168 hours. Overall, the herein assessed parameters have evidenced that the biosolids leachate diluted up to 60% had positive effect on (i.e., it stimulated) seedling growth and germination. However, phytotoxic effect was observed when it was applied without any dilution, since it reduced seed germination and growth parameters. Therefore, the lower the leachate concentration, the higher the Lactuca sativa root growth, a fact that highlights the phytotoxic effect of this leachate.